Conductive particles, their manufacturing method and conductive material containing same

JP7641231B2Active Publication Date: 2025-03-06NIPPON CHEMICAL IND CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021556145
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-15
Filing Date
2020-11-12
Publication Date
2025-03-06
Estimated Expiration
2040-11-12

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、接続抵抗が低く、かつ、接続信頼性の高い導電性粒子を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641231000003
    Figure 0007641231000003
  • Figure 0007641231000001
    Figure 0007641231000001
  • Figure 0007641231000002
    Figure 0007641231000002
Patent Text Reader

Abstract

Electrically conductive particles according to the present invention are obtained by forming electrically conductive layers on the surfaces of core material particles. The electrically conductive particles exhibit a highest value of compressive hardness of not less than 14700 N / mm2 and exhibit a highest value of compressive hardness at a compression rate of less than 5%. An average value of compressive hardness at a compression rate of 20-50% is not less than 1300 N / mm2 but less than 5000 N / mm2. The ratio of the highest value of compressive hardness with respect to the average value of compressive hardness at a compression rate of 20-50% is 1.5-50.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to conductive particles and conductive materials containing the same. [Background technology]

[0002] Conductive particles used as conductive materials in anisotropic conductive materials such as anisotropic conductive films and anisotropic conductive pastes are generally known to have a conductive layer made of metal formed on the surface of core particles, and this conductive layer provides electrical connection between electrodes and wiring.

[0003] When electrodes are connected under pressure using such conductive particles, it is necessary to remove the oxide film formed on the electrode surface in order to achieve electrical continuity, and the conductive particles are required to have a hardness that can withstand initial pressure. For example, Patent Document 1 discloses a conductive particle that can reduce connection resistance and increase connection reliability by making the ratio of the compression hardness at 10% compression to the compression hardness at 50% compression within a specific range by including a crosslinkable monomer having multiple ethylenically unsaturated groups in the resin particles that are the core material. However, in the initial stage of pressure connection between electrodes, the characteristics of the conductive layer as well as the characteristics of the core material particles are likely to have an effect.

[0004] From this viewpoint, Patent Document 2 describes that a conductive particle having a conductive layer including a crystal layer having a nickel-phosphorus crystal structure has a compression hardness of a specific value or more when compressed by 5%. Patent Document 3 describes a conductive particle having a conductive part with a plurality of protrusions on the outer surface, the proportion of (111) faces of the protrusions being 50% or more in X-ray diffraction, and the average maximum diameter of the base being 1 nm or more and 500 nm or less. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] WO2014 / 007334 [Patent Document 2] JP 2013-214511 A [Patent Document 3] JP 2016-119304 A Summary of the Invention [Problem to be solved by the invention]

[0006] Both Patent Document 2 and Patent Document 3 aim to reduce connection resistance and increase connection reliability when electrodes are electrically connected by improving the characteristics of the conductive layer to eliminate the oxide film formed on the electrode and conductive layer and to obtain conductive particles that increase the contact area between the electrode and conductive particles after connection, but there is room for further improvement.

[0007] Therefore, an object of the present invention is to provide conductive particles having lower connection resistance and higher connection reliability than ever before. [Means for solving the problem]

[0008] As a result of extensive research to solve the above-mentioned problems, the present inventors discovered that a conductive layer having a hardness sufficient to remove the oxide film formed on the electrode at the initial stage of pressure connection of the electrodes, and conductive particles having a hardness ratio of the conductive particles after connection that satisfies a specific range, can reduce connection resistance and also have excellent connection reliability, and thus completed the present invention.

[0009] That is, the present invention provides a conductive particle having a conductive layer formed on the surface of a core particle, the conductive particle having a maximum compressive hardness of 14700 N / mm 2 The maximum compressive hardness is observed when the compression ratio is less than 5%, and the average compressive hardness at a compression ratio of 20% to 50% is 1300N / mm 2 More than 5000N / mm 2 and the ratio of the maximum compression hardness to the average compression hardness at a compression rate of 20% or more and 50% or less is 1.5 or more and 50 or less.

[0010] The present invention also provides a method for producing conductive particles, which involves forming a conductive layer on the surface of a core particle by an electroless plating method, and which includes a step of adding a sulfur compound to an electroless plating reaction solution during the formation of the conductive layer. Effect of the Invention

[0011] According to the present invention, it is possible to provide conductive particles having low connection resistance and high connection reliability. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is an SEM image of the conductive particles obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The conductive particles of the present invention have a maximum compression hardness (hereinafter sometimes referred to as "K value") of 14700 N / mm 2 More than 16000N / mm 2 The maximum compressive hardness is 30,000 N / mm or more, and the compressibility is less than 5%, preferably at a compressibility of 1%, 2%, 3% or 4%. 2 It is preferable that: The compression hardness in the present invention is a value calculated by measuring the load value F (N) when a load is applied to a conductive particle of radius R (mm) at a loading rate of 2.23 mN / sec using a micro-compression testing machine (e.g., MCTM-500 manufactured by Shimadzu Corporation) and calculating the load value F (N) according to the following formula. Compressive hardness (N / mm 2 )=(3 / √2)×F×S -3 / 2 ×R -1 / 2 Here, the radius R (mm) of the conductive particle is a value calculated from the average particle diameter described later, and the compression ratio is the rate of change in length in the particle diameter direction, and is the ratio of the compression displacement S (mm) to the average particle diameter (mm).

[0014] Furthermore, the conductive particles of the present invention have an average compression hardness of 1300 N / mm at a compression ratio of 20% or more and 50% or less. 2 More than 5000N / mm 2 Less than 2000 to 3500 N / mm 2 The ratio of the maximum compression hardness to the average compression hardness at a compression rate of 20% to 50% is 1.5 to 50, preferably 2 to 30, and particularly preferably 3 to 15. Here, the average value of the compression hardness when the compression ratio is 20% or more and 50% or less means the average value of the K values ​​when the compression ratio is 20%, 30%, 40% and 50%.

[0015] In the present invention, it is preferable that the ratio of the K value at a compression rate of 3% to the K value at a compression rate of 40% is 1.5 or more and 70 or less, particularly 3 or more and 50 or less, in order to obtain conductive particles with low connection resistance and high connection reliability.

[0016] Since the conductive particles of the present invention have the property of being hard at the beginning of compression and becoming flexible when further compressed as described above, it is possible to sufficiently remove the oxide film formed on the electrode at the initial stage of pressure connection of the electrodes, thereby making it possible to reduce the connection resistance. In addition, since the conductive particles become flexible after pressure connection, the contact area with the electrode can be maintained, and the connection reliability is also excellent.

[0017] The conductive particles of the present invention are obtained by forming a conductive layer on the surface of a core particle. The core particles may be inorganic or organic, as long as they are particulate. Examples of inorganic core particles include metal particles such as gold, silver, copper, nickel, palladium, and solder, alloys, glass, ceramics, silica, metal or nonmetal oxides (including hydrates), metal silicates including aluminosilicates, metal carbides, metal nitrides, metal carbonates, metal sulfates, metal phosphates, metal sulfides, metal acid salts, metal halides, and carbon. On the other hand, examples of organic core particles include thermoplastic resins such as natural fibers, natural resins, polyethylene, polypropylene, polyvinyl chloride, polystyrene, polybutene, polyamide, polyacrylic acid esters, polyacrylonitrile, polyacetal, ionomers, and polyesters, alkyd resins, phenolic resins, urea resins, benzoguanamine resins, melamine resins, xylene resins, silicone resins, epoxy resins, and diallyl phthalate resins. These may be used alone or in combination of two or more.

[0018] The core particles may be composed of both inorganic and organic materials instead of the above-mentioned inorganic and organic materials. When the core particles are composed of both inorganic and organic materials, the existence mode of the inorganic and organic materials in the core particles may be, for example, a core made of an inorganic material and a shell made of an inorganic material covering the surface of the core, or a core made of an organic material and a shell made of an inorganic material covering the surface of the core, such as a core-shell type configuration. In addition, a blend type configuration in which an inorganic material and an organic material are mixed or randomly fused in one core particle may be mentioned. As the core particles composed of both inorganic and organic materials, the materials constituting the inorganic core particles or organic core particles described above can be used. The core particles may be composed of each of the inorganic and organic materials alone, or may be composed of two or more inorganic and organic materials in combination.

[0019] The core particles are preferably made of a resin, more preferably a thermoplastic resin, and by using a core made of such a material, the dispersion stability of the particles can be improved, and the appropriate elasticity can be exerted to improve the electrical conductivity when electrically connecting electronic circuits.

[0020] When an organic substance is used as the core particle, it is preferable that the core particle does not have a glass transition temperature or that the glass transition temperature is more than 100°C, because the shape of the core particle is easily maintained in the anisotropic conductive connection step and the shape of the core particle is easily maintained in the step of forming a metal film. When the core particle has a glass transition temperature, the glass transition temperature is preferably 200°C or less, because the conductive particles are easily softened in the anisotropic conductive connection and the contact area is increased, making it easier to obtain electrical continuity. From this viewpoint, when the core particle has a glass transition temperature, the glass transition temperature is more preferably more than 100°C and less than 180°C, and particularly preferably more than 100°C and less than 160°C. The glass transition temperature can be determined, for example, as the intersection point of the tangent of the original baseline and the inflection point in the baseline shift portion of the DSC curve obtained by differential scanning calorimetry (DSC).

[0021] In the case where an organic substance is used as the core particle, if the organic substance is a highly crosslinked resin, the glass transition temperature is hardly observed even when the above-mentioned method is used to measure up to 200°C. In this specification, such particles are also referred to as particles having no glass transition point, and such core particles may be used in the present invention. Specific examples of the core particle material having no glass transition temperature can be obtained by copolymerizing the monomer constituting the organic substance exemplified above with a crosslinkable monomer. Examples of crosslinkable monomers include tetramethylene di(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethylene oxide di(meth)acrylate, tetraethylene oxide (meth)acrylate, 1,6-hexane di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, trimeterolpropane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, tetramethylolmethane tri(meth)acrylate, Examples of such hard organic materials include polyfunctional (meth)acrylates such as tetramethylolmethane tetra(meth)acrylate, tetramethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol di(meth)acrylate, glycerol tridi(meth)acrylate, etc., polyfunctional vinyl monomers such as divinylbenzene and divinyltoluene, silane-containing monomers such as vinyltrimethoxysilane, trimethoxysilylstyrene, γ-(meth)acryloxypropyltrimethoxysilane, etc., and monomers such as triallyl isocyanurate, diallyl phthalate, diallyl acrylamide, diallyl ether, etc. In particular, in the field of COG (Chip on Glass), core particles made of such hard organic materials are often used.

[0022] There is no particular limitation on the shape of the core particles. In general, the core particles are spherical. However, the core particles may be in a shape other than spherical, such as fibrous, hollow, plate-like or needle-like, and may have a large number of protrusions on the surface or may be amorphous. In the present invention, spherical core particles are preferred because they have excellent filling properties and are easy to coat with metal.

[0023] The conductive layer formed on the surface of the core particle is made of a metal having electrical conductivity. Examples of the metal constituting the conductive layer include metals such as gold, platinum, silver, copper, iron, zinc, nickel, tin, lead, antimony, bismuth, cobalt, indium, titanium, antimony, bismuth, germanium, aluminum, chromium, palladium, tungsten, and molybdenum, as well as metal compounds such as ITO and solder. Among these, gold, silver, copper, nickel, palladium, and solder are preferred because they have low electrical resistance, and nickel, gold, nickel alloys, and gold alloys are particularly preferred. The metal may be one type, or two or more types may be used in combination.

[0024] The conductive layer may have a single layer structure or a laminate structure made up of multiple layers. In the case of a laminate structure made up of multiple layers, it is preferable that the outermost layer is at least one selected from nickel, gold, silver, copper, palladium, a nickel alloy, a gold alloy, a silver alloy, a copper alloy, and a palladium alloy. The conductive layer does not have to cover the entire surface of the core particle, and may cover only a part of it. When only a part of the surface of the core particle is covered, the covered part may be continuous, or may be discontinuously covered in an island shape, for example. The thickness of the conductive layer is preferably 0.1 nm or more and 2000 nm or less, more preferably 1 nm or more and 1500 nm or less. When the conductive particle has a protrusion described later, the height of the protrusion is not included in the thickness of the conductive layer. In the present invention, the thickness of the conductive layer can be measured by cutting the particle to be measured into two pieces and observing the cross section of the cut surface with a SEM.

[0025] The average particle diameter of the conductive particles is preferably 0.1 μm or more and 50 μm or less, more preferably 1 μm or more and 30 μm or less. When the average particle diameter of the metal-coated particles is within the above range, it is easy to ensure conduction between the opposing electrodes without causing a short circuit in a direction different from that between the opposing electrodes. In the present invention, the average particle diameter of the conductive particles is a value measured using a scanning electron microscope (SEM). Specifically, the average particle diameter of the conductive particles is measured by the method described in the examples. The particle diameter is the diameter of a circular conductive particle image. When the conductive particles are not spherical, the particle diameter refers to the longest length (maximum length) of the line segments that cross the conductive particle image.

[0026] When the conductive particles have protrusions on their surfaces, the height of the protrusions is preferably 20 nm to 1000 nm, more preferably 50 nm to 800 nm. The number of protrusions depends on the particle size of the conductive particles, but it is advantageous in terms of further improving the conductivity of the conductive particles to have a number of protrusions of preferably 1 to 20,000, more preferably 5 to 5,000 per conductive particle. The length of the base of the protrusion is preferably 5 nm to 1000 nm, more preferably 10 nm to 800 nm. The length of the base of the protrusion refers to the length along the surface of the conductive particle at the site where the protrusion is formed when measured using an electron microscope image in a cross-sectional view of the particle, and the height of the protrusion refers to the shortest distance from the base of the protrusion to the apex of the protrusion. In addition, when one protrusion has multiple apexes, the highest apex is taken as the height of the protrusion. The length of the base of the protrusion and the height of the protrusion are arithmetic average values ​​measured for 20 different particles observed by an electron microscope.

[0027] The shape of the conductive particles is not particularly limited, depending on the shape of the core particles. For example, it may be fibrous, hollow, plate-like or needle-like, and may have many protrusions on its surface or may be amorphous. In the present invention, it is preferable that the conductive particles are spherical or have many protrusions on their outer surface, in terms of excellent filling and connectivity. In particular, the conductive particles tend to have a large compression hardness at the beginning of compression when the conductive particles have a large protrusion on their outer surface.

[0028] Methods for forming a conductive layer on the surface of core particles include dry methods using deposition, sputtering, mechanochemical, hybridization, etc., and wet methods using electrolytic plating, electroless plating, etc. Also, a conductive layer may be formed on the surface of core particles by combining these methods.

[0029] In the present invention, it is preferable to form a conductive layer on the surface of the core particles by electroless plating, since this makes it easy to obtain conductive particles having the desired compression hardness.

[0030] Hereinafter, a case where a nickel-phosphorus plating layer is formed as the conductive layer will be described. When a conductive layer is formed on the surface of a core particle by electroless plating, it is preferable that the surface of the core particle has a precious metal ion trapping ability or is surface-modified to have a precious metal ion trapping ability. The precious metal ion is preferably a palladium or silver ion. Having a precious metal ion trapping ability means that the precious metal ion can be trapped as a chelate or salt. For example, when an amino group, an imino group, an amide group, an imide group, a cyano group, a hydroxyl group, a nitrile group, a carboxyl group, or the like is present on the surface of the core particle, the surface of the core particle has a precious metal ion trapping ability. When the surface is modified to have a precious metal ion trapping ability, for example, a method described in JP-A-61-64882 can be used.

[0031] Such core particles are used to support precious metals on their surfaces. Specifically, the core particles are dispersed in a dilute acidic aqueous solution of a precious metal salt such as palladium chloride or silver nitrate. This allows precious metal ions to be captured on the particle surface. The concentration of the precious metal salt is 100% per m of the particle surface area. 2 1x10 -7 ~1×10 -2 A molar range is sufficient. The core particles with the captured precious metal ions are separated from the system and washed with water. The core particles are then suspended in water, and a reducing agent is added to reduce the precious metal ions. This causes the precious metal to be supported on the surface of the core particles. Examples of reducing agents that can be used include sodium hypophosphite, sodium borohydride, potassium borohydride, dimethylamine borane, hydrazine, and formalin, and it is preferable to select one of these based on the constituent material of the desired conductive layer.

[0032] Before capturing precious metal ions on the surface of the core particles, the core particles may be subjected to a sensitization treatment to adsorb tin ions onto the surface of the particles. To adsorb tin ions onto the surface of the particles, for example, the surface-modified core particles may be placed in an aqueous solution of stannous chloride and stirred for a predetermined period of time.

[0033] The thus pretreated core particles are then subjected to a conductive layer forming process. There are two types of conductive layer forming process: a process for forming a conductive layer having protrusions, and a process for forming a conductive layer with a smooth surface. First, the process for forming a conductive layer having protrusions will be described.

[0034] In the process of forming the conductive layer having protrusions, the following first and second steps are performed. The first step is an electroless nickel plating step in which an aqueous slurry of core particles is mixed with an electroless nickel plating bath containing a dispersant, nickel salt, a reducing agent, a complexing agent, etc. In this first step, the plating bath self-decomposes at the same time as the conductive layer is formed on the core particles. This self-decomposition occurs in the vicinity of the core particles, so that the self-decomposition products are captured on the surface of the core particles during the formation of the conductive layer, forming the nuclei of the microprojections, and at the same time forming the conductive layer. The protrusions grow from the nuclei of the microprojections that have been generated.

[0035] In the first step, the above-mentioned core particles are sufficiently dispersed in water, preferably in the range of 0.1 to 500 g / L, more preferably in the range of 1 to 300 g / L, to prepare an aqueous slurry. The dispersion operation can be performed by normal stirring, high-speed stirring, or using a shear dispersion device such as a colloid mill or a homogenizer. Ultrasonic waves may also be used in the dispersion operation. If necessary, a dispersant such as a surfactant may be added in the dispersion operation. Next, the aqueous slurry of the core particles that has been subjected to the dispersion operation is added to an electroless nickel plating bath containing a nickel salt, a reducing agent, a complexing agent, and various additives, to perform the first electroless plating step.

[0036] Examples of the dispersant include nonionic surfactants, amphoteric surfactants, and / or water-soluble polymers. Examples of the nonionic surfactants include polyoxyalkylene ether surfactants such as polyethylene glycol, polyoxyethylene alkyl ether, and polyoxyethylene alkyl phenyl ether. Examples of the amphoteric surfactants include betaine surfactants such as alkyldimethyl acetate betaine, alkyldimethylcarboxymethyl acetate betaine, and alkyldimethylamino acetate betaine. Examples of the water-soluble polymers include polyvinyl alcohol, polyvinylpyrrolidinone, and hydroxyethyl cellulose. These dispersants can be used alone or in combination of two or more. The amount of the dispersant used varies depending on the type, but is generally 0.5 to 30 g / L relative to the volume of the liquid (electroless nickel plating bath). In particular, it is preferable that the amount of the dispersant used is in the range of 1 to 10 g / L relative to the volume of the liquid (electroless nickel plating bath) from the viewpoint of further improving the adhesion of the conductive layer.

[0037] As the nickel salt, for example, nickel chloride, nickel sulfate, or nickel acetate is used, and the concentration is preferably in the range of 0.1 to 50 g / L. As the reducing agent, for example, the same as those used for reducing the precious metal ions described above can be used, and is selected based on the constituent material of the target undercoat film. When a phosphorus compound, for example, sodium hypophosphite, is used as the reducing agent, the concentration is preferably in the range of 0.1 to 50 g / L.

[0038] As the complexing agent, for example, a carboxylic acid (salt) such as citric acid, hydroxyacetic acid, tartaric acid, malic acid, lactic acid, gluconic acid or its alkali metal salt or ammonium salt, an amino acid such as glycine, an amine acid such as ethylenediamine or alkylamine, other ammonium, EDTA or pyrophosphoric acid (salt) having a complexing effect on nickel ions is used. These can be used alone or in combination of two or more. The concentration is preferably in the range of 1 to 100 g / L, more preferably 5 to 50 g / L. The preferred pH of the electroless nickel plating bath at this stage is in the range of 3 to 14. The electroless nickel plating reaction begins quickly when the aqueous slurry of the core particles is added, and is accompanied by the generation of hydrogen gas. The first step is terminated when the generation of hydrogen gas is completely no longer observed.

[0039] In the second step, following the first step, (i) a first aqueous solution containing one of nickel salt, reducing agent, and alkali, and a second aqueous solution containing the remaining two are used, or (ii) a first aqueous solution containing nickel salt, a second aqueous solution containing reducing agent, and a third aqueous solution containing alkali are used, and these aqueous solutions are added simultaneously and over time to the solution of the first step to perform electroless nickel plating. When these solutions are added, the plating reaction starts again, and the conductive layer formed can be controlled to a desired film thickness by adjusting the amount of the solutions added. After the addition of the electroless nickel plating solution is completed, the solution temperature is maintained and stirring is continued for a while after the generation of hydrogen gas is completely stopped, to complete the reaction.

[0040] In the case of (i) above, it is preferable to use a first aqueous solution containing a nickel salt and a second aqueous solution containing a reducing agent and an alkali, but this combination is not limited to this. In this case, the first aqueous solution does not contain a reducing agent or an alkali, and the second aqueous solution does not contain a nickel salt. As the nickel salt and the reducing agent, those mentioned above can be used. As the alkali, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide can be used. The same applies to the case of (ii) above.

[0041] In the case of (ii) above, the first to third aqueous solutions each contain a nickel salt, a reducing agent, and an alkali, and each aqueous solution does not contain the other two components other than the respective components.

[0042] In either case of (i) or (ii), the concentration of the nickel salt in the aqueous solution is preferably 10 to 1000 g / L, particularly preferably 50 to 500 g / L. When a phosphorus compound is used as the reducing agent, the concentration of the reducing agent is preferably 100 to 1000 g / L, particularly preferably 100 to 800 g / L. When a boron compound is used as the reducing agent, the concentration is preferably 5 to 200 g / L, particularly preferably 10 to 100 g / L. When hydrazine or a derivative thereof is used as the reducing agent, the concentration is preferably 5 to 200 g / L, particularly preferably 10 to 100 g / L. The concentration of the alkali is preferably 5 to 500 g / L, particularly preferably 10 to 200 g / L.

[0043] The second step is carried out continuously after the first step is completed, but instead, the first step and the second step may be carried out intermittently. In this case, after the first step is completed, the core particles and the plating solution are separated by a method such as filtration, the core particles are newly dispersed in water to prepare an aqueous slurry, an aqueous solution in which a complexing agent is dissolved in a concentration range of preferably 1 to 100 g / L, more preferably 5 to 50 g / L, is added thereto, and a dispersant is dissolved in a concentration range of preferably 0.5 to 30 g / L, more preferably 1 to 10 g / L to prepare an aqueous slurry, and the second step of adding each of the aqueous solutions to the aqueous slurry may be carried out. In this way, a conductive layer having protrusions can be formed.

[0044] Next, a process for forming a conductive layer having a smooth surface will be described below. The conductive layer having a smooth surface can be formed by reducing the concentration of the nickel salt in the electroless nickel plating bath in the first step of the treatment for forming the conductive layer having the protrusions. That is, the nickel salt may be, for example, nickel chloride, nickel sulfate, or nickel acetate, and the concentration is preferably in the range of 0.01 to 0.5 g / L. A conductive layer having a smooth surface can be formed by performing the first and second steps described above except for reducing the concentration of the nickel salt in the electroless nickel plating bath.

[0045] In the present invention, it is preferable to add a sulfur compound during the formation of the conductive layer, since this tends to result in conductive particles with a large compression hardness in the initial stage of compression. Sulfur compounds include 2-mercaptobenzothiazole, 2-mercaptobenzoxazole, 2-mercaptobenzimidazole, 2-mercapto-1-methylimidazole, thioglycolic acid, thiodiglycolic acid, cysteine, saccharin, thiamine nitrate, sodium N,N-diethyl-dithiocarbamate, 1,3-diethyl-2-thiourea, dipyridine, N-thiazole-2-sulfamylamide, 1,2,3-benzotriazole-2-thiazoline-2- Examples of sulfur compounds include thiol, thiazole, thiourea, ethylenethiourea, thiozole, sodium thioindoxylate, o-sulfonamidobenzoic acid, sulfanilic acid, acid orange, methyl orange, naphthionic acid, naphthalene-α-sulfonic acid, 1-naphthol-4-sulfonic acid, Scheffer's acid, sulfadiazine, ammonium thiocyanate, potassium thiocyanate, sodium thiocyanate, rhodanine, ammonium sulfide, sodium sulfide, and ammonium sulfate. These sulfur compounds can be used alone or in combination of two or more. The amount of sulfur compound used is preferably such that the total sulfur compound concentration in the electroless plating reaction solution is 0.01 mass ppm or more and 100 mass ppm or less, and more preferably such that the total sulfur compound concentration in the electroless plating reaction solution is 0.1 mass ppm or more and 50 mass ppm or less. If the amount of sulfur compound used is too small, the effect of increasing the compression hardness at the beginning of compression is difficult to be exhibited, and if the amount is too large, the compression hardness becomes high from the middle to the end of compression, which is not preferable.

[0046] The sulfur compound may be added at any time during the formation of the conductive layer, but is preferably added during the second step. In particular, it is preferable to start the addition 5 to 20 minutes after the start of the second step, since this makes it easier to increase the compression hardness at the initial stage of compression. The sulfur compound may be added all at once, or may be added in multiple portions, or may be added continuously, but adding the entire amount at once is preferable since this makes it easier to increase the compression hardness at the initial stage of compression. In the case of the method of adding the sulfur compound all at once, although it depends on the scale of the reaction system, for example, when a 1L reactor is used, the addition time is preferably 30 seconds or less, more preferably 15 seconds or less. There is no lower limit to the addition time, but it is usually 0.1 seconds or more, or 0.5 seconds or more. By adding the sulfur compound within this range, the compression hardness at the beginning of compression can be easily increased. In the present invention, by adding a sulfur compound in this manner in the process of forming a conductive layer having the above-mentioned protrusions, the protrusions tend to become larger, and therefore it is possible to obtain the effect of further increasing the compression hardness at the initial stage of compression. In this manner, the conductive particles of the present invention are obtained.

[0047] When the conductive particles of the present invention are used as a conductive filler for a conductive adhesive as described below, the surfaces of the conductive particles can be further coated with an insulating resin in order to prevent short circuits between the conductive particles. The insulating resin coating is formed so that the surfaces of the conductive particles are not exposed as much as possible when no pressure or the like is applied, and is broken by the heat and pressure applied when bonding two electrodes with the conductive adhesive, exposing at least the protrusions on the surfaces of the conductive particles. The thickness of the insulating resin can be about 0.1 to 0.5 μm. The insulating resin may cover the entire surfaces of the conductive particles, or may only cover a part of the surfaces of the conductive particles.

[0048] As the insulating resin, a wide variety of resins known in the art can be used, including, for example, phenol resin, urea resin, melamine resin, allyl resin, furan resin, polyester resin, epoxy resin, silicone resin, polyamide-imide resin, polyimide resin, polyurethane resin, fluororesin, polyolefin resin (e.g., polyethylene, polypropylene, polybutylene), polyalkyl(meth)acrylate resin, poly(meth)acrylic acid resin, polystyrene resin, acrylonitrile-styrene-butadiene resin, vinyl resin, polyamide resin, polycarbonate resin, polyacetal resin, ionomer resin, polyethersulfone resin, polyphenyloxide resin, polysulfone resin, polyvinylidene fluoride resin, ethyl cellulose, and cellulose acetate.

[0049] Methods for forming an insulating coating layer on the surface of conductive particles include chemical methods such as coacervation, interfacial polymerization, in situ polymerization, and liquid curing coating; physico-mechanical methods such as spray drying, air suspension coating, vacuum deposition coating, dry blending, hybridization, electrostatic coalescence, melting dispersion cooling, and inorganic encapsulation; and physico-chemical methods such as interfacial precipitation.

[0050] The conductive particles of the present invention thus obtained are suitably used, for example, as an anisotropic conductive film (ACF), a heat seal connector (HSC), a conductive material for connecting electrodes of a liquid crystal display panel to a circuit board of a driving LSI chip, etc. In particular, the conductive particles of the present invention are suitably used as a conductive filler for a conductive adhesive.

[0051] The conductive adhesive is preferably used as an anisotropic conductive adhesive that is disposed between two substrates on which a conductive base material is formed, and that adheres the conductive base material to conduct electricity by heating and pressurization. This anisotropic conductive adhesive contains the conductive particles of the present invention and an adhesive resin. The adhesive resin can be used without any particular limitation as long as it is insulating and is used as an adhesive resin. It may be either a thermoplastic resin or a thermosetting resin, and it is preferable that the adhesive performance is expressed by heating. Such adhesive resins include, for example, a thermoplastic type, a thermosetting type, an ultraviolet curing type, and the like. In addition, there are so-called semi-thermosetting types that show intermediate properties between the thermoplastic type and the thermosetting type, and composite types of a thermosetting type and an ultraviolet curing type. These adhesive resins can be appropriately selected according to the surface characteristics of the circuit board or the like to be adhered and the form of use. In particular, an adhesive resin that includes a thermosetting resin is preferable because it has excellent material strength after adhesion.

[0052] Specific examples of adhesive resins include those prepared using as a base material one or a combination of two or more selected from ethylene-vinyl acetate copolymer, carboxyl-modified ethylene-vinyl acetate copolymer, ethylene-isobutyl acrylate copolymer, polyamide, polyimide, polyester, polyvinyl ether, polyvinyl butyral, polyurethane, SBS block copolymer, carboxyl-modified SBS copolymer, SIS copolymer, SEBS copolymer, maleic acid-modified SEBS copolymer, polybutadiene rubber, chloroprene rubber, carboxyl-modified chloroprene rubber, styrene-butadiene rubber, isobutylene-isoprene copolymer, acrylonitrile-butadiene rubber (hereinafter referred to as NBR), carboxyl-modified NBR, amine-modified NBR, epoxy resin, epoxy ester resin, acrylic resin, phenolic resin, and silicone resin. Among these, styrene-butadiene rubber and SEBS are preferable as thermoplastic resins because they have excellent reworkability. As thermosetting resins, epoxy resins are preferable. Of these, epoxy resins are most preferred because of their advantages of high adhesive strength, excellent heat resistance and electrical insulation, low melt viscosity, and ability to connect at low pressure.

[0053] As the epoxy resin, any commonly used epoxy resin can be used as long as it is a polyhydric epoxy resin having two or more epoxy groups in one molecule. Specific examples include novolac resins such as phenol novolac and cresol novolac, polyhydric phenols such as bisphenol A, bisphenol F, bisphenol AD, resorcin, and bishydroxydiphenyl ether, polyhydric alcohols such as ethylene glycol, neopentyl glycol, glycerin, trimethylolpropane, and polypropylene glycol, polyamino compounds such as ethylenediamine, triethylenetetramine, and aniline, and polyvalent carboxy compounds such as adipic acid, phthalic acid, and isophthalic acid, and glycidyl-type epoxy resins obtained by reacting epichlorohydrin or 2-methylepichlorohydrin. In addition, aliphatic and alicyclic epoxy resins such as dicyclopentadiene epoxide and butadiene dimer diepoxide can be mentioned. These can be used alone or in combination of two or more.

[0054] From the viewpoint of preventing ion migration, it is preferable to use high-purity adhesive resins in which impurity ions (Na, Cl, etc.) and hydrolyzable chlorine are reduced as the various adhesive resins mentioned above.

[0055] The amount of the conductive particles of the present invention used in the anisotropic conductive adhesive is usually 0.1 to 30 parts by mass, preferably 0.5 to 25 parts by mass, and more preferably 1 to 20 parts by mass, per 100 parts by mass of the adhesive resin component. By keeping the amount of the conductive particles within this range, increases in connection resistance and melt viscosity are suppressed, connection reliability is improved, and connection anisotropy can be sufficiently ensured.

[0056] In addition to the conductive particles and adhesive resin described above, the anisotropic conductive adhesive may contain additives known in the art. The amount of the additives may be within a range known in the art. Examples of other additives include tackifiers, reactive assistants, epoxy resin curing agents, metal oxides, photoinitiators, sensitizers, curing agents, vulcanizing agents, anti-degradation agents, heat resistance additives, thermal conductivity improvers, softeners, colorants, various coupling agents, or metal deactivators.

[0057] Examples of tackifiers include rosin, rosin derivatives, terpene resins, terpene phenol resins, petroleum resins, coumarone-indene resins, styrene resins, isoprene resins, alkylphenol resins, and xylene resins. Examples of reactive auxiliaries, i.e., crosslinking agents, include polyols, isocyanates, melamine resins, urea resins, utropines, amines, acid anhydrides, and peroxides. As epoxy resin curing agents, any agent having two or more active hydrogens per minute can be used without any particular limitations. Specific examples include polyamino compounds such as diethylenetriamine, triethylenetetramine, metaphenylenediamine, dicyandiamide, and polyamidoamine; organic acid anhydrides such as phthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and pyromellitic anhydride; and novolac resins such as phenol novolac and cresol novolac. These can be used alone or in combination of two or more. If necessary, a latent curing agent may be used. Examples of usable latent curing agents include imidazoles, hydrazides, boron trifluoride-amine complexes, sulfonium salts, aminimides, polyamine salts, dicyandiamide, and modified products thereof. These can be used alone or in combination of two or more.

[0058] The anisotropic conductive adhesive is manufactured using a manufacturing device commonly used in the technical field. For example, the conductive particles of the present invention and the adhesive resin, as well as a curing agent and various additives as necessary, are mixed together in an organic solvent when the adhesive resin is a thermosetting resin, and melt-kneaded at a temperature above the softening point of the adhesive resin, specifically preferably about 50 to 130°C, more preferably about 60 to 110°C, when the adhesive resin is a thermoplastic resin. The anisotropic conductive adhesive thus obtained may be applied as a coating or in the form of a film. EXAMPLES

[0059] The present invention will be further described below with reference to examples, but the scope of the present invention is not limited to these examples. The properties in the examples were measured by the following methods. (1) Compressive hardness of conductive particles (K value) The K value was determined by the above-mentioned method using a microcompression tester (Shimadzu Corporation, MCTM-500). In addition, the K value when the compression rate is X% may be expressed as "X% K value." (2) Average particle size 200 particles were randomly extracted from a scanning electron microscope (SEM) photograph of the measurement subject, and the particle diameters were measured at a magnification of 10,000 times, and the arithmetic mean value was taken as the average particle diameter.

[0060] Example 1 (1) Pretreatment Spherical benzoguanamine-based soft resin particles with an average particle size of 3.0 μm were used as core particles. 9 g of the particles were added to 200 mL of conditioner aqueous solution ("Cleaner Conditioner 231" manufactured by Rohm and Haas Electronic Materials) while stirring. The concentration of the conditioner aqueous solution was 40 mL / L. The solution was then stirred for 30 minutes at a liquid temperature of 60°C while applying ultrasonic waves to the core particles to modify their surface and disperse them. The aqueous solution was filtered, and the core particles were repulped and washed once to form a 200 mL slurry. 0.1 g of stannous chloride was added to the slurry. The mixture was stirred at room temperature for 5 minutes to perform a sensitization treatment in which tin ions are adsorbed on the surface of the core particles. The aqueous solution was then filtered, and the core particles were repulped and washed once to form a 200 mL slurry and maintained at 60°C. 1.5 mL of a 0.11 mol / L aqueous palladium chloride solution was added to the slurry. The mixture was stirred at 60°C for 5 minutes to activate the core particles, capturing palladium ions on their surfaces. The aqueous solution was then filtered, and the core particles were repulped and washed with hot water once to make a 100mL slurry. 10mL of 0.5g / L dimethylamine borane aqueous solution was added, and the mixture was stirred for 2 minutes while applying ultrasonic waves to obtain a slurry of pretreated core particles.

[0061] (2) Preparation of plating bath 3 L of an electroless nickel-phosphorus plating bath consisting of an aqueous solution containing 5 g / L sodium tartrate, 2 g / L nickel sulfate hexahydrate, 10 g / L trisodium citrate, 0.1 g / L sodium hypophosphite, and 2 g / L polyethylene glycol was prepared and heated to 70°C.

[0062] (3) Electroless plating The slurry of the pretreated core particles was added to this electroless plating bath and stirred for 5 minutes, after which it was confirmed that hydrogen bubbling had ceased. To this slurry, 420 mL of a 224 g / L nickel sulfate aqueous solution and 420 mL of a mixed aqueous solution containing 210 g / L sodium hypophosphite and 80 g / L sodium hydroxide were continuously added separately by a metering pump at an addition rate of 2.5 mL / min for each, and electroless plating was started. 10 minutes after the start, 2-mercaptobenzothiazole was added in 1 second so that the final concentration in the solution was 7.5 mass ppm, and 40 minutes after the start, the addition rates of the two types of aqueous solutions were both 4.7 mL / min. After the entire amount of the nickel sulfate aqueous solution and the mixed aqueous solution of sodium hypophosphite and sodium hydroxide was added, stirring was continued for 5 minutes while maintaining the temperature at 70°C. The solution was then filtered, and the filtrate was washed three times and then dried in a vacuum dryer at 110°C to obtain conductive particles having a conductive layer made of a nickel-phosphorus alloy. The obtained conductive particles had an average particle size of 3.22 μm, a conductive layer thickness of 110 nm, and had large protrusions. An SEM image is shown in FIG. 1. The obtained conductive particles showed the highest compression hardness at a compression ratio of 3%. The compression hardness at each compression ratio is shown in Table 1.

[0063] Example 2 Conductive particles were produced in the same manner as in Example 1, except that 2-mercaptobenzoxazole was added instead of 2-mercaptobenzothiazole in the (3) electroless plating treatment. The average particle size of the obtained conductive particles was 3.22 μm, the thickness of the conductive layer was 110 nm, and the conductive particles had large protrusions. The obtained conductive particles showed the highest compression hardness at a compression ratio of 4%. The compression hardness at each compression ratio is shown in Table 1.

[0064] Example 3 Conductive particles were produced in the same manner as in Example 1, except that the concentration of nickel sulfate hexahydrate in (2) Preparation of plating bath was changed from 2 g / L to 0.1 g / L. The average particle size of the obtained conductive particles was 3.22 μm, the thickness of the conductive layer was 110 nm, and the conductive particles had a smooth shape without protrusions. The obtained conductive particles showed the highest compression hardness at a compression ratio of 3%. The compression hardness at each compression ratio is shown in Table 1.

[0065] Comparative Example 1 (1) Pretreatment Spherical benzoguanamine-based soft resin particles with an average particle size of 3.0 μm were used as core particles. 9 g of the particles were added to 200 mL of conditioner aqueous solution ("Cleaner Conditioner 231" manufactured by Rohm and Haas Electronic Materials) while stirring. The concentration of the conditioner aqueous solution was 40 mL / L. The solution was then stirred for 30 minutes at a liquid temperature of 60°C while applying ultrasonic waves to the core particles to modify their surface and disperse them. The aqueous solution was filtered, and the core particles were repulped and washed once to form a 200 mL slurry. 0.1 g of stannous chloride was added to the slurry. The mixture was stirred at room temperature for 5 minutes to perform a sensitization treatment in which tin ions are adsorbed on the surface of the core particles. The aqueous solution was then filtered, and the core particles were repulped and washed once to form a 200 mL slurry and maintained at 60°C. 1.5 mL of a 0.11 mol / L aqueous palladium chloride solution was added to the slurry. The mixture was stirred at 60°C for 5 minutes to activate the core particles, capturing palladium ions on their surfaces. The aqueous solution was then filtered, and the core particles were repulped and washed with hot water once to make a 100mL slurry. 10mL of 0.5g / L dimethylamine borane aqueous solution was added, and the mixture was stirred for 2 minutes while applying ultrasonic waves to obtain a slurry of pretreated core particles.

[0066] (2) Preparation of plating bath 3 L of an electroless nickel-phosphorus plating bath consisting of an aqueous solution containing 5 g / L sodium tartrate, 2 g / L nickel sulfate hexahydrate, 10 g / L trisodium citrate, 0.1 g / L sodium hypophosphite, and 2 g / L polyethylene glycol was prepared and heated to 70°C. (3) Electroless plating

[0067] The slurry of the pretreated core particles was added to this electroless plating bath and stirred for 5 minutes, after which it was confirmed that hydrogen bubbling had ceased. To this slurry, 420mL of a 224g / L nickel sulfate aqueous solution and 420mL of a mixed aqueous solution containing 210g / L sodium hypophosphite and 80g / L sodium hydroxide were continuously added separately by a metering pump at an addition rate of 2.5mL / min, and electroless plating was started. After the entire amount of the nickel sulfate aqueous solution and the mixed aqueous solution of sodium hypophosphite and sodium hydroxide was added, stirring was continued for 5 minutes while maintaining the temperature at 70°C. The liquid was then filtered, and the filtrate was washed three times and then dried in a vacuum dryer at 110°C to obtain conductive particles having a conductive layer made of a nickel-phosphorus alloy. The average particle size of the obtained conductive particles was 3.22μm, the thickness of the conductive layer was 110nm, and the conductive particles had protrusions. The obtained conductive particles also showed the highest compression hardness at a compression ratio of 2%. Table 1 shows the compression hardness at each compression ratio.

[0068] Comparative Example 2 (1) Pretreatment Spherical benzoguanamine-based soft resin particles with an average particle size of 3.0 μm were used as core particles. 9 g of the particles were added to 200 mL of conditioner aqueous solution ("Cleaner Conditioner 231" manufactured by Rohm and Haas Electronic Materials) while stirring. The concentration of the conditioner aqueous solution was 40 mL / L. The solution was then stirred for 30 minutes at a liquid temperature of 60°C while applying ultrasonic waves to the core particles to modify their surface and disperse them. The aqueous solution was filtered, and the core particles were repulped and washed once to form a 200 mL slurry. 0.1 g of stannous chloride was added to the slurry. The mixture was stirred at room temperature for 5 minutes to perform a sensitization treatment in which tin ions are adsorbed on the surface of the core particles. The aqueous solution was then filtered, and the core particles were repulped and washed once to form a 200 mL slurry and maintained at 60°C. 1.5 mL of a 0.11 mol / L aqueous palladium chloride solution was added to the slurry. The mixture was stirred at 60°C for 5 minutes to activate the core particles, capturing palladium ions on their surfaces. The aqueous solution was then filtered, and the core particles were repulped and washed with hot water once to make a 100mL slurry. 10mL of 0.5g / L dimethylamine borane aqueous solution was added, and the mixture was stirred for 2 minutes while applying ultrasonic waves to obtain a slurry of pretreated core particles.

[0069] (2) Preparation of plating bath 3 L of an electroless nickel-phosphorus plating bath was prepared from an aqueous solution containing 5 g / L of sodium tartrate, 2 g / L of nickel sulfate hexahydrate, 10 g / L of trisodium citrate, 0.1 g / L of sodium hypophosphite, and 2 g / L of polyethylene glycol, and 2-mercaptobenzothiazole was added to the solution so that the final solution had a concentration of 7.5 ppm by mass. The solution was then heated to 70°C.

[0070] (3) Electroless plating The slurry of the pretreated core particles was added to this electroless plating bath and stirred for 5 minutes, after which it was confirmed that hydrogen bubbling had ceased. To this slurry, 420mL of a 224g / L nickel sulfate aqueous solution and 420mL of a mixed aqueous solution containing 210g / L sodium hypophosphite and 80g / L sodium hydroxide were continuously added separately by a metering pump at an addition rate of 2.5mL / min, and electroless plating was started. After the entire amount of the nickel sulfate aqueous solution and the mixed aqueous solution of sodium hypophosphite and sodium hydroxide was added, stirring was continued for 5 minutes while maintaining the temperature at 70°C. The liquid was then filtered, and the filtrate was washed three times and then dried in a vacuum dryer at 110°C to obtain conductive particles having a nickel-phosphorus alloy film. The average particle size of the obtained conductive particles was 3.05μm, the thickness of the conductive layer was 25nm, and the conductive particles had protrusions. The obtained conductive particles also showed the highest compression hardness at a compression ratio of 2%. Table 1 shows the compression hardness at each compression ratio.

[0071] [Table 1]

[0072] [Evaluation of connection resistance and connection reliability] Using the conductive particles of the examples and comparative examples, the connection resistance and connection reliability were evaluated by the following method. An insulating adhesive containing 100 parts by weight of epoxy resin, 150 parts by weight of hardener, and 70 parts by weight of toluene was mixed with 15 parts by weight of the coated particles obtained in the examples and comparative examples to obtain an insulating paste. This paste was applied to a silicone-treated polyester film using a bar coater, and then the paste was dried to form a thin film on the film. The obtained thin film-formed film was placed between a glass substrate with aluminum vapor-deposited on the entire surface and a polyimide film substrate with a copper pattern formed at a pitch of 50 μm to prepare a sample for measuring the conductive resistance, and electrical connection was made. The connection resistance value of this sample was measured at room temperature (25°C and 50% RH). The lower the connection resistance value, the better the connection resistance of the conductive particles can be evaluated. The results are shown in Table 2. In addition, a pressure cooker test was performed in which the samples for measuring the conduction resistance were arranged in an airtight container and subjected to an environment of 121°C temperature, 100% relative humidity, and 2 atmospheres for 10 hours. After the pressure cooker test, the connection resistance values ​​of the samples were measured at room temperature (25°C, 50% RH). The smaller the difference in connection resistance values ​​before and after the pressure cooker test, the higher the connection reliability of the conductive particles can be evaluated. The results are shown in Table 2.

[0073] [Table 2]

[0074] From these results, it can be seen that the conductive particles obtained in Examples 1 to 3 have lower resistance values ​​than the conductive particles obtained in Comparative Examples 1 and 2. It can also be seen that the conductive particles obtained in Examples 1 to 3 maintain good conductivity without an increase in connection resistance value even after the pressure cooker test.

Claims

1. In the conductive particles, a conductive layer is formed on the surface of a core particle, The maximum compression hardness of the conductive particles is 14700 N / mm 2 or more, and the compressive hardness is maximum at a compressibility of less than 5%, The average compression hardness at a compression ratio of 20% to 50% is 1300 N / mm 2 More than 5000N / mm 2 Less than Conductive particles having a ratio of 3 or more and 15 or less of the maximum compression hardness to the average compression hardness at a compression ratio of 20% or more and 50% or less.

2. 2. The conductive particles according to claim 1, wherein the ratio of the compression hardness at a compression rate of 3% to the compression hardness at a compression rate of 40% is 1.5 or more and 70 or less.

3. The conductive particle according to claim 1 or 2, wherein the conductive layer has a thickness of 0.1 nm or more and 2000 nm or less.

4. 4. The conductive particle according to claim 1, which has protrusions on its outer surface.

5. 4. The conductive particle according to claim 1, which has a smooth outer surface.

6. A conductive material comprising the conductive particles according to any one of claims 1 to 5 and an insulating resin.

Citation Information

Patent Citations

  • Conductive electroless plating powder and method for manufacturing the same

    JP2004131801A

  • Conductive particle, conductive material, and connection structure

    JP2013214511A

  • Method of producing organic inorganic hybrid particle, conductive particle, conductive material and connection structure

    JP2015110743A

  • Conductive particle, conductive material and connection structure

    JP2016119304A

  • Conductive particle, conductive material and connection structure

    JP2017069191A